(untitled) (Research, Society and Development, 2022)
The family business plays a prominent role in the national and global economic sphere. However, family businesses tend to have a shorter lifespan compared to other companies, as they do not find a balance between management, succession and professionalization. In order to have longevity and continuous progress, it is necessary to plan and execute strategies outlined in the succession period that must be exercised in the long term, in addition to inserting professionalization at the time of succession so that the heirs are prepared to assume the position of family administrator with responsibility. . In this context, the present research was developed with the objective of showing how the transition of family business management is planned. For this, the research carried out the diagnosis in a family microenterprise in the financial sector in the city of Salgueiro - PE, through a qualitative research, which was developed through an interview with the manager of the aforementioned company. The results reveal that the entire professionalized transition process has been working for some time, while interpersonal relationships influence the process. They also show that positive characteristics of family management are being carried out in parallel with the succession and show points considered worrying that the management itself believes is a necessary period to reach the desired level. Therefore, the studied company is considerably qualified and qualified to keep the transition planning in execution and is moving in the right direction considering possible adjustments for the improvement of management.